Determining Value at Risk using Extreme Value Theory on a Financial Data Set - Stevo Gjorgiev, Aneta Gacovska - Barandovska (Union of Mathematicians of Macedonia, 2023)
Extreme value theory has a wide range of applications. The paper considers application of extreme value theory in the area of nancial ows. Our data set has been processed using two di erent methods, block maxima and peak over the threshold method. We compare the obtained results for the risk measures and draw conclusions on the behavior of the nancial ows for di erent time intervals.
Keywords: Extreme value theory, block maxima, peak over the threshold method, risk measures, Macedonian Stock Exchange, MB10 index.